The determination of 230Th in the sediments: Sedimentation in Matang Mangrove Forest, Taiping, Perak - Leong, H.F.; B.Y., Kamaruzzaman (Penerbit Universiti Sains Malaysia, 2004)
Mangrove forests are a buffer zone between the coast and the ocean. One of the important functions is to provide a mechanism for trapping sediment. Suspended sediment is introduced to coastal areas by river discharge, dumping of dredged material and resuspension of bottom sediment by waves and ships (Wolanski, 1994). However, the sedimentary processes on Malaysian mangroves are not well documented.